Crystal OH mediating pathway for hydrogen peroxide production via two-electron water oxidation in non-carbonate electrolytes - Ruilin Wang; Hao Luo; Chengyu Duan; Huimin Liu; Mengdi Sun; Quan Zhou; Zheshun Ou; Yinglong Lu; Guanghui Luo; Jimmy C. Yu; Zhuofeng Hu (Nature Communications)
Abstract Water oxidation presents a promising avenue for hydrogen peroxide (H2O2) production. However, the reliance on alkaline bicarbonate electrolytes as an intermediate has limitations, such as H2O2 decomposition and a narrow pH effectiveness range (7–9), restricting its utility across wider pH ranges. This study unveils a crystal OH mediating pathway that stabilizes SO4OH* as a crucial intermediate. Basic copper carbonate (Cu2(OH)2CO3) tablets, commonly found on cultural relics, exhibit the capability to generate H2O2 in neutral or acidic non-bicarbonate electrolytes. By leveraging this crystal OH mediating strategy, considerable H2O2 production in Na2SO4 electrolytes is achievable. Notably, the H2O2 production rate can reach 64.35 μmol h−1 at 3.4 V vs. RHE in a 50 mL 0.5 M Na2SO4 electrolyte. This research underscores the importance of crystal part in catalyst in catalyzing the 2e− water oxidation reaction, offering valuable insights for future investigations.